Deskilling and degradation of labour in contemporary capitalism: the continuing relevance of Braverman. (1st April 2015) - ,; ,
Abstract : This article examines the continuing relevance of Harry Braverman's thesis on the degradation of work to the new circumstances of the twenty-first century. It argues that, despite claims that the standardisation and deskilling of work that characterised the Taylorist/Fordist period have given way to new forms of knowledge-based production and an integration of mental and manual labour, the concept of degradation is still relevant. New conditions of production demand a new and more versatile kind of worker who is able to meet the requirements of production processes that require intensive use of information technologies, are globally dispersed and related to the consumption of products with a high technological density. Nevertheless, the new conditions of capital accumulation are still based on the same laws of value and require intensive control and surveillance of the worker. This control, however, takes new forms under regimes of flexible accumulation, and is founded in managerial strategies built on workers' involvement and participation. Ensuring workers' compliance with such strategies requires the creation of the new kinds of subjectivity. The article goes on to discuss the education reforms required to produce such subjectivities, and the transformation of pedagogical processes and teaching labour that are necessary to achieve these reforms. It concludes by reflecting on the implications of the resulting individualisation of workers' subjectivities for class solidarity.